Pengaruh Return Policy Leniency dan Seller Reputation Terhadap Purchase Decision Dimediasi Consumer Trust - Puspita Chairun Nisa; Veni Helen Virgita Hutagalung (Jurnal Bisnis dan Pemasaran Digital, 2022)
Purpose: This study aims to determine and analyze the effect of return policy leniency and seller reputation on purchase decisions mediated by consumer trust on C2C e-commerce platform users. Based on signaling theory, consumer trust built by return policy leniency and seller reputation will increase purchase decisions. Method: The population of this study is consumers who have shopped at non-official Shopee stores. The sampling method used was non-probability with the purposive sampling method. Data analysis method used is path analysis PLS-SEM. Result: The results showed that the return policy leniency affected customer trust and purchase decisions; Seller reputation affected customer trust and purchase decisions. Limitations: The limitation of this research is that the researcher only uses two variables that affect consumer confidence. In addition, researchers also have not focused on product categories purchased by e-commerce consumers. The number of respondents used was 170 respondents, not enough to represent all e-commerce consumers in Bekasi and Jakarta. Contribution: This research can be a suggestion and input for online vendors to seriously consider the potential of consumer trust in changing return policies into buying behavior by providing extra guarantees such as return policy leniency in order to gain consumer trust and increase sales.